Anidulafungin for the treatment of candidaemia caused by Candida parapsilosis: Analysis of pooled data from six prospective clinical studies. Issue 10 (9th June 2017) - Kontoyiannis, Dimitrios P.; Bassetti, Matteo; Nucci, Marcio; Capparella, Maria Rita; Yan, Jean L.; Aram, Jalal; Hogan, Patricia A.
Summary: Concerns with echinocandin use for infections caused by Candida parapsilosis complex species have driven the need for data to support echinocandin clinical efficacy in such patients. Data from six prospective studies were pooled to assess efficacy and safety of anidulafungin in patients with candidaemia caused by C. parapsilosis . Patient‐level data were pooled from patients with microbiologically confirmed candidaemia due to C. parapsilosis treated with anidulafungin. Patients received a 200 mg intravenous (IV) loading dose of anidulafungin (day 1) and 100 mg daily thereafter. IV treatment could be switched to oral azole therapy after ≥5 or ≥10 days. Primary endpoint was global response at end of IV therapy (EOIVT). Seventy patients had candidaemia caused by C. parapsilosis . Global response was 77.1% (95% CI: 67.3, 87.0) at EOIVT and 70.0% (95% CI: 59.3, 80.7) at end of treatment. Three of 55 isolates (with MICs available) were resistant to anidulafungin (MIC ≥8 mg/L). All‐cause mortality was 5.7% (n=4/70) by day 14 and 14.3% (n=10/70) by day 28. IV anidulafungin was effective for the treatment of C. parapsilosis candidaemia in this population, consistent with efficacy previously demonstrated for other Candida species. (ClinicalTrials.gov identifiers: NCT00496197, NCT00548262, NCT00537329, NCT00689338, NCT00806351, NCT00805740).